Validation of a Persian Version of the Oral Health Impact Profile (OHIP-14) - N Navabi; N Nakhaee; A Mirzadeh (Iranian Journal of Public Health, 2010)
"nBackground: The oral health-related quality of life indicators are increasingly used to measure the impact of the oral conditions on quality of life. One of the most used indicators is the Oral Health Impact Profile (OHIP-14), but it has never been applied in Iran. The aim of this study was to validate the usage of OHIP-14 among Iranians. "nMethods: A cross-sectional study was performed in Kerman (Iran). A consecutive sample (n= 400) of the Kerman Dental School Clinics attending patients participated in this study. All participants self-completed the translated OHIP-14. Reliability analyses, validity tests, and responsiveness were carried out to evaluate the psychometric properties of the OHIP-14. "nResults: The reliability coefficient (Cronbach's alpha) of the OHIP-14 was above the recommended 0.7 threshold and considered excellent (alpha: 0.85). The coefficient of the test-retest reliability measured by ICC was 0.88 (CI 95%: 0.80-0.93). Poorer oral condition was strongly associated with OHIP scores of the patients, supporting construct validity. Moreover, for evaluation of responsiveness, the ES was measured to be 0.43 and the SRM was 0.67. "nConclusions: The Persian version of OHIP-14 is a precise, valid and reliable instrument for assessing oral health-related quality of life among Persian population